P8 Epidemiology of tuberculosis in norfolk. (15th November 2017) - Bhamani, A; Terrington, D; Phillips, R
Abstract : The incidence of tuberculosis in England has shown a year-on-year decline over the past four years. The main burden of disease has been concentrated in larger urban areas. The East of England is an area of low prevalence and in 2015, had the lowest rate of TB cases notified per 1 00 000 people (6.2). London, the West Midlands and the North-West had the highest rates in the country. The population demographic of Norfolk shows a variation when compared to the rest of England. In 2011, 21.4% of Norfolk's population was aged 65 or over compared with 16.5% in England. Similarly, 94.3% of people in Norfolk were identified as white compared to 87.5% in England. 1 We hypothesised that these differences would be reflected in the demographics of patients treated for Tuberculosis at the Norfolk and Norwich University Hospital (NNUH). We analysed data over a 3 year period between 2014 and 2016. While most patients were diagnosed and treated locally, patients had been diagnosed elsewhere and moved to the local area after commencing treatment. One patient moved abroad following diagnosis. Our incidence of Tuberculosis was significantly lower than the national rate. Forty-six patients were diagnosed with TB in the 3 year period. This equates to 2.47 new cases per 1 00 000 people compared to 10.5 per 1 00 000 nationally in 2015. Four cases were Isoniazid resistant (8.7% compared to 6.9% nationally). There was one case of multi drug-resistant TB. Fourteen cases did not have microbiological cultures. In our patient group, 67.3% were born outside the UK compared to 72.5% nationally. Twenty-one of the twenty-three patients aged less than 40 were born abroad. However, all of the seven patients 65 and above were UK-born. Additionally, of the twenty patients with extra-pulmonary disease (with or without pulmonary involvement), only two were born within the UK. These trends are similar to those seen nationally. Furthermore, the incidence of TB locally peaked in the 25–29 age group reflecting national figures. 2 Our analysis shows that contrary to our hypothesis, there is no significant difference in the TB population in a low-incidence area compared to high-incidence areas. References: http://www.cprenorfolk.org.uk/wp-content/uploads/2012/05/Demography-and-Information-in-Norfolk.pdf http://www.tbalert.org/wp-content/uploads/2016/09/PHE_TB_Annual_Report_2016.pdf